Infective endocarditis risk in patients with bicuspid aortic valve: systematic review and meta-analysis - Couto Pereira, Sara Cristina (2023)
© 2023 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)